Tannic acid directly targets pyruvate kinase isoenzyme M2 to attenuate colon cancer cell proliferation. Issue 11 (27th September 2018) - Yang, Peng; Ding, Guo-Bin; Liu, Wen; Fu, Rong; Sajid, Amin; Li, Zhuoyu
Abstract : Tannic acid, which ubiquitously exists in grapes and green tea, binds to K433 to trigger dissociation of PKM2 tetramers and further block the metabolic activity of PKM2 to suppress colorectal cancer cell proliferation. Abstract : Tannic acid (TA), a naturally occurring polyphenolic acid that is primarily found in grapes and green tea, exhibits potent antioxidant and anticarcinogenic characteristics. However, the underlying molecular mechanisms and targets of TA, which are responsible for cancer prevention, remain elusive. In the present study, we used TA-functionalized magnetite nanoparticles to identify pyruvate kinase isoenzyme M2 (PKM2) as the direct target of TA. We report that TA selectively inhibits the pyruvate kinase activity of PKM2, rather than protein kinase activity and PKM2 expression, to suppress colorectal cancer (CRC) cell proliferation. Furthermore, we had discovered that lysine residue 433 (K433) is a selective druggable site. Through direct binding to lysine residue 433, TA triggers the dissociation of PKM2 tetramers and further blocks the metabolic activity of PKM2. Notably, TA has no effect on PKM1 activity as TA does not bind to it. Taken together, these findings show that TA is worthy of consideration as a promising PKM2 inhibitor for the prevention of CRC.